Fostering prosperity at the local scale: Outcomes of urban policy for deprived neighbourhoods in Germany - Uwe Neumann; Serife Yasar (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
Traditional urban policy focuses mainly on redevelopment measures. Germany's Social City programme incorporates urban regeneration with support to local communities in deprived neighbourhoods. We use microdata on household characteristics from the German Socio-Economic Panel (SOEP) and microdata on housing prices from the RWI GEO-RED to assess the policy effects on household income and housing markets. Drawing on propensity score matching, we find that household incomes among programme areas have not been affected. However, hedonic pricing models reveal significant effects on housing prices and rents. – – Stadterneuerungsprogramme konzentrieren sich traditionell überwiegend auf die städtebauliche Sanierung. Das deutsche Programm "Soziale Stadt" verband die Stadterneuerung mit der Unterstützung der Bevölkerung und des lokalen Gemeinwesens in benachteiligten Stadtteilen. Wir verwenden Mikrodaten zu Haushaltsmerkmalen aus dem Sozio-oekonomischen Panel (SOEP) und Mikrodaten aus dem RWI GEO-RED, um die Auswirkungen der "Sozialen Stadt" auf Haushaltseinkommen, Mieten und Wohnungspreise in den Programmgebieten zu untersuchen. Mit Hilfe von Matching-Analysen stellen wir fest, dass die Haushaltseinkommen nicht beeinflusst wurden. Hedonische Preismodelle zeigen dagegen signifikant positive Auswirkungen auf Wohnungspreise und Mieten.
Keywords: C21; O18; R23; R31; R58; 330; Segregation; urban policy; matching; hedonic pricing models